Calculating Techniques for The Contrast of Images Which Have Different Illuminations - Al-Zuky, A. A. D.; Zuheri, S. S.S.; Al- Shujare, K. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The distortion, which occurs to the image often affects the existing amount of information, weakens its sharpness, decreases its contrast, thus leads to overlapping details of the various regions, and decreases image resolution. Test images are used to determine the image quality and ability of different visual systems, as we depended in our study on test image, half black and half white. Contrast was studied in the petition so as to propose several new methods for different contrasts in the edge of images where the results of technical differences would identify contrast image under different lighting conditions.